2015
DOI: 10.1098/rsif.2014.1074
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic behaviour of collagen networks in cell–matrix interactions and mechanosensation

Abstract: The mechanical properties of extracellular matrix proteins strongly influence cell-induced tension in the matrix, which in turn influences cell function. Despite progress on the impact of elastic behaviour of matrix proteins on cell-matrix interactions, little is known about the influence of inelastic behaviour, especially at the large and slow deformations that characterize cell-induced matrix remodelling. We found that collagen matrices exhibit deformation rate-dependent behaviour, which leads to a transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 55 publications
7
43
0
Order By: Relevance
“…The results from this study support the growing body of experimental and theoretical work that indicates that the fibrous nature of biological gels is responsible for enhanced long-distance cell mechanosensing compared to nonfibrous gels [14][15][16][17]30,[46][47][48]. Several of these theoretical studies have found that the mechanosensing length scale of a cell increases when fibers are accounted for in the model [14,30,46,48].…”
Section: Discussionsupporting
confidence: 74%
“…The results from this study support the growing body of experimental and theoretical work that indicates that the fibrous nature of biological gels is responsible for enhanced long-distance cell mechanosensing compared to nonfibrous gels [14][15][16][17]30,[46][47][48]. Several of these theoretical studies have found that the mechanosensing length scale of a cell increases when fibers are accounted for in the model [14,30,46,48].…”
Section: Discussionsupporting
confidence: 74%
“…Tissue contraction depends on the combination of cell density and type, 21 matrix type and associated physical properties, 4244 and physical boundary conditions. 22,43 Culture surface coating with glutaraldehyde, polyethylenimine, or poly-L-lysine may be applied to improve construct adherence and minimize contraction. 45,46 …”
Section: Resultsmentioning
confidence: 99%
“…Notably, the design of the grid-supported collagen model and the low cell plating density used for laterally supported and underlying supported gels, enabled study of cell extension formation and collagen remodeling of individual cells, which is in contrast to the more complex mechanics that are measured with higher plating densities and the combinatorial effects of multiple interacting cells. The inferences derived from this model indicate that collagen compaction precedes cell extension formation, which relates to the irreversible inelastic deformation properties of collagen gels described earlier [73,74]. PAK1 phosphorylation has been used as an indicator of PAK1 kinase activity [49] and effector function in actin assembly [29].…”
Section: Discussionmentioning
confidence: 98%